Demokrasi dan partisipasi politik: Tantangan dan peluang di era digital - Agung saputra, Indra Wahyu (Maliki Interdisciplinary Journal, 2026)
Democracy is a system of government that places the people as the holders of supreme sovereignty. In the digital era, political participation has undergone significant transformations influenced by developments in information technology and social media. This study aims to analyze the dynamics of democracy and political participation in the digital era, encompassing the opportunities offered by technology as well as the challenges faced, particularly the spread of hoaxes, disinformation, and polarization. The study used qualitative methods with a systematic literature review approach to various academic sources related to digital democracy and citizen engagement. The results show that social media opens up broader spaces for participation, but also creates the risk of eroding public trust in democratic institutions. Strengthening digital literacy based on Pancasila values ​​and comprehensive regulations are needed to ensure a healthy democracy in the digital era. This research is expected to contribute to policy development and the study of public management science in Indonesia.